The Relationship between Maternal Mental Health Problems and Domestic Violence with Mentally Retarded Children Behavioral Problems - Azita Pourvahed; Mojtaba Amiri-Majd (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objectives: Given that children are the future of society with immediate owners, their health and disease in health and disease tomorrow's society and future generations will have signifiant effects. Therefore it is necessary to pay more attention to their physical and mental health and fundamental steps for the prevention and treatment of mental disorders and their behavior is removed. This study aimed to investigate the relationship between mental health problems of mothers and children facing domestic violence were mentally retarded children with behavior problems. Material and Methods: This study was descriptive-correlation was performed. The study sample consisted of all mentally retarded children 7 to 12 years and their mothers who were in schools with intellectual disability had been studying in the academic year 94-95. The sampling method was multi-stage cluster sampling in this study. The sample consisted of 150 students with intellectual disability who were selected based on criteria for the study. The questionnaire includes demographic information, a checklist related symptoms (SCL.25), behavioral problems Conners Rating Scale and the Conflct Tactics Scale. To analyze the data Pearson correlation and multiple regression analysis at the signifiant level were used. Results: The fidings showed that between mother and child's exposure to domestic violence, mental health problems mentally retarded children with behavioral problems and there is a signifiant positive relationship and can be accessed through the mother's mental health problems and family violence, behavioral problems in children with mental retardation predicted. Conclusion: The results of this study indicate that between mental health problems and domestic violence mother mentally retarded children with behavioral problems are related.